Modelling of urban tourism : a case study of Ho Chi Minh City (HCMC). - Ho, Shu Lian. (2009)
Tourism in cities exists within a wider regional and national context in terms of spatial patterns of visitor behaviour and distribution of tourism resources. Tourism in historic cities has been modelled by Ashworth and Tunbridge (1990) as the shaping and location of historic resources that have a close relationship with the contemporary functions of their urban context. However, this model is derived from medium-sized European cities, with no stated relevance to Asian historic cities.